2018
DOI: 10.1039/c7tb02748f
|View full text |Cite
|
Sign up to set email alerts
|

Stable star polymer nanolayers and their thermoresponsiveness as a tool for controlled culture and detachment of fibroblast sheets

Abstract: Star polymer nanolayers were successfully used as surfaces for fibroblast adhesion and proliferation, followed by their detachment in the form of a cell sheet, controlled by a temperature decrease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Based on the obtained values and on the hydrodynamic diameters of the star polymers in acetone, which were in the range of 20-30 nm [60], it could be concluded that stars were formed not as monolayers, but rather in the form of multilayers. A similar situation was observed for layers made of stars with poly[oligo(ethylene glycol) methacrylate] arms where the obtained layer thickness made of the star polymer was in the range of 58-59.5 nm [59].…”
Section: Layersupporting
confidence: 78%
See 1 more Smart Citation
“…Based on the obtained values and on the hydrodynamic diameters of the star polymers in acetone, which were in the range of 20-30 nm [60], it could be concluded that stars were formed not as monolayers, but rather in the form of multilayers. A similar situation was observed for layers made of stars with poly[oligo(ethylene glycol) methacrylate] arms where the obtained layer thickness made of the star polymer was in the range of 58-59.5 nm [59].…”
Section: Layersupporting
confidence: 78%
“…These signals were better visible at deconvoluted lines of XPS spectra (Supporting Information, Figure S1A,B). Bromine atoms originated from the PArOx core and from the ends of the arms in case of star layers and only from the ends of PDMAEMA chains for linear layers [59]. For comparison, the benzophenone functionalized layers (sample SBPH) did not show the presence of bromine at all (Supporting Information, Figure S1C).…”
Section: Physicochemical Characterization Of the Obtained Pdmaema Layersmentioning
confidence: 99%
“…The cell sheets can then be used as 2D building blocks in tissue engineering and regenerative medicine [ 6 , 7 ]. Besides extensively discussed and investigated poly( N -isopropyl acrylamide) (PNIPAm) gel [ 8 ] and brush [ 9 ] coatings, thermoresponsive brushes based on poly(oxazoline)s (POx) [ 10 , 11 ], poly[oligo(ethylene glycol) methacrylate]s (POEGMAs) [ 12 , 13 , 14 ] and poly(glycidyl ether)s (PGEs) [ 15 , 16 ] have shown to be among the most suitable thermoresponsive coatings for cell sheet fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, such membranes can also be exploited for the direct transfer of detaching cell sheets onto in vitro tissue culture scaffolds or for the regeneration of tissues in vivo. Whereas both “grafting-from” and “grafting-to” methods have been used to manufacture thermoresponsive PNIPAm coatings on most of the common culture substrate materials, reports on promising POx and POEGMA brush coatings are still mainly limited to glass substrates [ 10 , 11 , 12 , 13 , 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cell engineering, thermoresponsive polymers based on oligo(ethylene glycol) methacrylates [111][112][113][114][115][116], oxazolines [117][118][119][120], and ethers [121,122] were also applied.…”
Section: Substrates and Scaffolds For Cell And Tissue Culturementioning
confidence: 99%